Circular RNAs: Emerging players in the pathogenesis of keloid - Yu, Xin; Zhu, Xueqing; Li, Linfeng; Gao, Guangcheng (Frontiers in Physiology, 2022)
Circular RNAs (circRNAs) are a new type of non-coding RNA originating from precursor messenger RNAs. Recent research has confirmed that circRNAs play a significant role in various biological and pathological processes, including cell viability, migration, and apoptosis. Emerging studies have demonstrated that deregulated circRNA-miRNA-mRNA interaction network plays a key role in the development of many diseases. Increasing evidence has highlighted the role of ncRNA’s (mainly miRNAs and lncRNAs) in the pathogenesis of keloid. Recently, several publications also indicated circRNAs contribute to keloid development. The discovery of circRNAs changed the current understanding of the biology of keloids It is crucial to elucidate a circRNA miRNA-mRNA network to understand the pathological mechanism of keloid. In the present review, we summarize the aberrant expression of regulatory roles of circRNAs in keloid. We discuss the potential clinical application of circRNAs in the diagnosis and treatment of keloid.